Manufacture and Characterization of Porous Ceramics Based On Clay Soil And Banana Frond Powder - Arianty, Lisa; Sitorus, Zuriah (Journal of Technomaterial Physics, 2022)
This work reports the manufacture and characterization of porous ceramics synthesized using clay and banana frond powder by employing the dry-pressing method. The clay and banana frond powder was filtered with a grain size of 200 mesh. Production of printed ceramics was made with the proportion of the combination of clay and banana frond powder of 100%:0%; 95%:5%; 90%:10%; 85%:15%; 80%:20%; 75%:25%; 70%:30%; 65%:35%; 60%:40%; 55%:45%; 50%:50% and heated with a sintering temperature of 1000Â°C with a holding time of 3 hours. The resulting ceramics are described by determining their actual properties (thickness, porosity, and shrinkage), mechanical properties (compressive strength and hardness), surface morphology and pore size (SEM), and base material (EDX). The results show that the mixed varieties of 50%:50% clay and banana frond powder have a density value of 1.22 g/cm3, a porosity of 41.31%, and heat loss of 11.41 %, compressive strength of 1.36 MPa, and hardness of 99.15 MPa. The surface morphology results showed that the sample has evenly distributed pore sizes of 10.54 m, 10.77 m, and 12.15 m, which is called a macroporous ceramic with a pore size of > 50 nm.